Recurrence plot-based dynamic analysis on electrochemical noise of the evolutive corrosion process. (1st August 2017) - Liu, Wei; Wang, Dongzhe; Chen, Xiaohua; Wang, Chunguang; Liu, Haiding
Highlights: Cross recurrence quantification measures detect possible dynamic transition from the uncorrelated noises. The cross recurrence plot pattern indicates different corrosion mechanism regarding distinctive impedance component. The synchronization index may be used to assess the corrosion degree during an evolutive process. Abstract: The cross recurrence plot (CRP) method was applied on the simultaneous current and voltage fluctuation time records in consideration of their possible nonlinear kinetics. Sequential cross recurrence quantification analysis (CRQA), CRP pattern recognition and synchronization analysis were used to screen the paralleled running from the uncorrelated oscillations, to recognize the impedance component, and to identify the synchronization type and degree in the dynamical view point. With the aid of the proposed approach, the sulfur-induced localized corrosion of the alloy 718 in the high temperature brine was detected and evaluated during the evolutive corrosion process.